Plan de exportación de bisutería vegetal de la empresa "Artesanías semillas amazónicas" a Estados Unidos - Salazar, Carla E. (2019)
The diversification of export products is essencial to take advantage of the opportunities of the competitive advantages that Ecuador has, the vegetal costume jewelery is considered a newest product by its making one hundred percent (100%) handcrafted. Through this export plan, we try to take advantage of an opportunity for growth within the craft market, since the artisans themselves take their manufactures to foreign markets, but in an inadequate way, that is, they do not do it directly, but rather to through intermediaries and through this proposal export directly.